A study on English translation of Vietnamese traditional medicine texts - Phạm, Thị Minh Chiên (University of Languages and International Studies, 2017)
This paper is intended to deal with the English translation of Vietnamese Traditional Medicine texts. It aims at clarifying and discussing some characteristics of VTM texts and then giving suggestions on strategies and techniques used in translating VTM texts and standardization of English translation of VTM. It also analyzes common mistakes and figures out the reasons for this present chaotic situation.